The antihyperlipidaemic and hepatoprotective effect of Ipomoea batatas L. leaves extract in high-fat diet rats - Nurkhasanah Mahfudh; Nanik Sulistyani; Muhammad Syakbani; Athifah Candra Dewi (Intelektual Pustaka Media Utama, 2021)
The administration of high-fat diets can increase the body's lipid level and damage the organs. Purple sweet potato leaf (Ipomoea batatas L.) was reported as an antioxidant against free radicals. This study aimed to observe the sweet potato leaf extract's activity on decreasing lipid profile and hepatoprotective effect in high-fat diet fed rats. The treatment animals were divided into five groups, namely normal control, high-fat diet (HFD) control, the treatment group of purple sweet potato leaf extract (SPLE) doses 100 mg/kg BW, 200 mg/kg BW and 400 mg/kg BW which fed with high-fat diet for 14 days and SPLE for 28 days. After treatment was completed, the blood was collected for the detection of cholesterol, triglyceride, serum glutamic oxaloacetic transaminase (SGOT), and serum glutamic pyruvate transaminase (SGPT). After that, the animals were sacrificed, and a liver histopathology observation was conducted using Haematoxylien and Eosin staining. The result showed a significant decrease in cholesterol and triglyceride levels (p≤0.05) compared to the negative group in all treated groups. The SGOT and SGPT enzymes in all of treatment groups were also found to decrease compared with HFD control. The result was confirmed by the histopathological observations. The finding suggested the potency of SPLE for antihyperlipidaemic and hepatoprotective agent.